(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the quality of conventional (unpasteurized) and pasteurized frozen cashew pulps according to their identity and quality standard (physicochemical and microbiological aspects). Thus, four cashew pulp brands were analyzed, two conventional (non-pasteurized) 1 and 2, and two pasteurized 3 and 4. The following parameters with respect to physical-chemical analyzes were determined: soluble solids content, total solids, pH, total acidity expressed in citric acid and ascorbic acid. The mycorbiological analyzes performed were coliforms at 35 °C and 45 °C, molds, yeasts and Salmonella. The results showed that all brands had levels of soluble solids, pH, total acidity expressed in citric acid and ascorbic acid according to the current legislation, with small oscillations between the brands. Microbiological analyzes revealed mold and yeast contamination above that allowed by current legislation. Thus, it is concluded that pasteurization cannot always be considered an effective method in the destruction of microorganisms in food, suggesting an improvement in equipment hygiene.